Creutzfeldt-Jakob disease and mad cows: lessons learnt from yeast cells (Swiss Medical Weekly, 2012)
Transmissible spongiform encephalopathies are fatal neurodegenerative diseases that affect mammals including humans. The proteinaceous nature of the infectious agent, the prion, and its propagation, challenge established dogmas in biology. It is now widely accepted that prion diseases are caused by unconventional agents principally composed of a misfolded host-encoded protein, PrP. Surprisingly, major break-throughs in prion research came from studies on functionally unrelated proteins in yeast and filamentous fungi. Aggregates composed of these proteins act as epigenetic elements of inheritance that can propagate their alternative states by a conformational switch into an ordered ß-sheet rich polymer just like mammalian prions. Since their discovery prions of lower eukaryotes have provided invaluable insights into all aspects of prion biogenesis. Importantly, yeast prions provide proof-of-principle that distinct protein conformers can be infectious and can serve as genetic elements that have the capacity to encipher strain specific information. As a powerful and tractable model system, yeast prions will continue to increase our understanding of prion-host cell interaction and potential mechanisms of protein-based epigenetic inheritance.